The foundation of «Mercurio Peruano» and the intellectual environment of 1918 - Arrizabalaga, Carlos (Mercurio Peruano, 2018)
The first decades of the 1900s caused a fertile intellectual environment in Peru, this was freely expressed in a wide range of journals of different genres. The desire to have their own magazine had been developed in the group of friends who would constitute the editorial staff of the magazine. However, this was not created to answer or counteract the ideas of Colónida or other magazines of different sign. The new Mercurio Peruano wanted to contribute its effort in correcting "the discontinuity and incoherence that were two great defects of our collective psychology", and for this reason, they proposed "to unify the work of our thinkers and our literati, making them concert towards national life". The success of the writing of the new El Mercurio was through the great opening of contributions (many of them came from the provinces), with the consequent variety of topics and subjects that made their reading really pleasant and interesting.